Risk evaluation of duodenoscope-associated infections in the Netherlands calls for a heightened awareness of device-related infections: a systematic review - Kwakman, Judith A.; Erler, Nicole S.; Vos, Margreet C.; Bruno, Marco J. (Endoscopy, 2021)
Background The risk of exogenous infections from endoscopic procedures is often cited as almost negligible (1 infection in 1.8 million procedures); however, this risk is based on older literature and does not seem to match the number of infectious outbreaks due to contaminated duodenoscopes reported after endoscopic retrograde cholangiopancreatography (ERCP). Using Dutch data, we aimed to estimate the minimum risk of duodenoscope-associated infection (DAI) and colonization (DAC) in patients undergoing ERCP.Methods A systematic literature search identified all DAI outbreaks in the Netherlands reported between 2008 and 2019. Included cases were confirmed by molecular matching of patient and duodenoscope cultures. Risk ratios were calculated based on the total number of ERCPs performed during the study period.Results Three outbreaks were reported and published between 2008 and 2018, including 21 confirmed DAI cases and 52 confirmed DAC cases. The estimated number of ERCPs performed during the same period was 181 209–227 006. The calculated minimum estimated DAI risk was approximately 0.01 % and the minimum estimated DAC risk was 0.023 %–0.029 %.Conclusions The estimated risk of DAI in Dutch ERCP practice was at least 180 times higher than previously published risk estimates. The actual risk is likely to be (much) higher due to underreporting of infections caused by multidrug-resistant organisms and sensitive bacteria. Greater awareness by healthcare personnel involved in endoscopy and endoscope cleaning is required, as well as innovative technical solutions to contain and ultimately eliminate DAIs.